2013
DOI: 10.1111/aas.12052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a physician‐staffed helicopter on a regional trauma system: a prospective, controlled, observational study

Abstract: IntroductionThis study aims to compare the trauma system before and after implementing a physician-staffed helicopter emergency medical service (PS-HEMS). Our hypothesis was that PS-HEMS would reduce time from injury to definitive care for severely injured patients.MethodsThis was a prospective, controlled, observational study, involving seven local hospitals and one level I trauma centre using a before and after design. All patients treated by a trauma team within a 5-month period (1 December 2009–30 April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 42 publications
4
48
1
Order By: Relevance
“…In a mature system, build on a belief that a survival benefit of the service is expected, we had expected better precision in dispatch or better availability. The findings are in line with a recent study from Denmark 12. Another recent study comparing the trauma centre in Oslo, Norway to the trauma centre in Stockholm, Sweden found an 8.2 times higher presence of pre‐hospital anaesthesiologists in Oslo (30.5%) as compared to Stockholm (3.7%) 13.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a mature system, build on a belief that a survival benefit of the service is expected, we had expected better precision in dispatch or better availability. The findings are in line with a recent study from Denmark 12. Another recent study comparing the trauma centre in Oslo, Norway to the trauma centre in Stockholm, Sweden found an 8.2 times higher presence of pre‐hospital anaesthesiologists in Oslo (30.5%) as compared to Stockholm (3.7%) 13.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, other benefits such as reduced need for secondary transfer and reduced mortality rates can be seen 12. However, due to the cost, limited availability of HEMS, and non‐negligible risk for both the crew and the patient, there is a growing focus on limiting over‐triage 15, 17, 18, 19, 20.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 7,8 have shown a similar demographic of a higher proportion of road traffic collisions occurring by night and also assaults. These assault victims may suffer blunt or penetrating trauma that may require enhanced medical care.…”
Section: Discussionmentioning
confidence: 55%
“…Advanced treatment was provided in more than two thirds of these missions, which cannot be expected from ambulance personnel or regular GPs. Indeed, many patients with serious conditions and a high rate of providing advanced medical treatment may indicate the need for an anesthesiologist or at least a physician well‐trained in emergency medicine; however, the benefit of physician‐staffed HEMS has been debated for decades 9, 13, 15, 21, 22. In addition, the advantage of an experienced anesthesiologist capable of early and sound clinical judgment may be of more value than performing advanced interventions, as the avoidance of an intervention is best practice in some cases.…”
Section: Discussionmentioning
confidence: 99%